Wage Differential of Informal Employment in Nepal - Chhetri, Santosh; Basnyat, Bhawana (Academia Research Journal, 2023)
The total number of occupations or positions held during the specified reference period constitutes informal employment. It is deemed that a person has an informal job or employment if their employment relationship is, legally or practically, exempt from national labor legislation, income taxation, social protection, or the right to specific employment benefits. In Nepal, the problem of informal work is growing, and the economic yardstick for measuring social justice is the wage gap. This research uses a logistic regression approach to examine the factors that influence informal employment in Nepal. The computation of the factors affecting informality and wage disparities in informal employment in Nepal was done using two estimating techniques. The daily salary is significantly negatively impacted by informal employment. The workers who participate in informality make less money per day than those who work in regular employment. The findings indicate a positive and statistically significant relationship between worker age and daily pay. Workers are more likely to make a daily wage the older they are. When the workers are of the janajati ethnic group, their daily wages increase. But the daily wage of workers is not much impacted by dalit laborers. Workers who are married are more likely than other workers to have greater daily pay. They are therefore favorably related to one another. The outcome also showed that the worker's daily income grows along with their level of education. As a result, there is an association.